Aplicação do modelo de Thirlwall para a Argentina e o Brasil de 1992-2006 - Balbé, Fabiane Frois (2008)
In the 90 s, Argentina and Brazil went through economical stabilization reforms, commercial flexibility and an integration in the prevailing external trade. In this context, this work aims at analyzing if the exports and imports are affected by changes both in the intern and extern income for the two economies from 1992 to 2006. Based on the Thirlwall Increase Model and using the literature techniques of unit root and co-integration, the long-term balance among the variables was tested: exportation and external income, importation and internal income. The Error Correction Mechanism was determined and in case of a serial autocorrelation, such a problem is corrected with Gauss Newton algorithm. For the economies studied it was concluded that exportations and importations are affected by changes in the external and internal incomes respectively. Brazil presented a higher importation flexibility-income than an exportation one, while Argentina showed a lower importation flexibility-income than an exportation one.